Developing new 'thinking-for-speaking' patterns in Greek as a foreign language: the role of proficiency and stays abroad. Issue 1 (2nd January 2017) - Andria, Maria; Serrano, Raquel
Abstract : The purpose of this study is to investigate the influence of first language thinking-for-speaking patterns on the acquisition of Greek as a second language (L2), as well as to determine whether proficiency level and stays in the target-language country have an effect on such influence. The participants ( N =50) were Spanish/Catalan learners of Greek who belonged to different proficiency groups (from A2.1 up to B2.1 of the Common European Framework of Reference) and had had stays in Greece of various durations (from a few weeks up to several years). The participants performed two tasks in their L2: a grammaticality judgement task and a picture description task, which included expressions that are encoded as a single verb in Greek but as a periphrasis in Spanish/Catalan, as well as in English (e.g. to be hungry, to be sleepy, to be embarrassed, etc.). A group of Greek native speakers ( N =15) also did the same tasks. The results indicate that L1 patterns were transferred to the L2 and that the performance of the L2 learners was significantly different from that of the native speakers'. Moreover, proficiency and time in Greece played a significant role in the acquisition of the patterns under analysis.